Design, fabrication, and physical properties analysis of laminated Low-E coated glass for retrofit window solutions - Nur-E-Alam M.; Vasiliev M.; Yap B.K.; Islam M.A.; Fouad Y.; Kiong T.S. (Elsevier Ltd, 2025)
The ever-growing demand for improved energy efficiency in buildings has stimulated a stream of research focused on innovative retrofit energy solutions. Laminated low emissivity (Low-E) type coated glass components can be used in retrofitting window systems for enhancing energy savings provided by the insulating properties of glass laminates containing these heat-mirror-type coatings. In particular, custom-designed double-silver low-E coatings embedded into the laminate structure (directly facing the polymer interlayers during and after the lamination) are of interest due to being protected from environmental exposure, enabling easy component transportation, storage, and window retrofits. In this study, we provide some details on the design of several reflector-type solar control low-E coatings of high environmental stability and demonstrate the feasibility of their fabrication on 3 mm thick glass substrates, followed by the lamination. We describe the optical properties of laminated structural glass components of potential usefulness for retrofitting window applications in new and existing buildings. Several thin-film coatings of a low-E type are deposited by using the RF magnetron sputtering technique and then subjected to lamination by using transparent epoxy and PVB materials, to be protected by a clear glass cover layer. The optical performance characteristics of these coatings (measured before and after lamination) elucidate the effects these lamination materials and cover glass thickness have on the final optical properties (leading to a slight reduction in the optical transmission in the visible spectral range, by around 8?10 % while retaining low thermal emissivity across the infrared spectral range). The outcomes of this research, if industrialized could contribute significantly to the development of sustainable building components and practices, and to acheiving a reduction in building energy consumption by way of enabling window retrofit operations at potentially reduced costs. ? 2024 The Author(s)